If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 2v = -2 Solving 2 + 2v = -2 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2v = -2 + -2 Combine like terms: 2 + -2 = 0 0 + 2v = -2 + -2 2v = -2 + -2 Combine like terms: -2 + -2 = -4 2v = -4 Divide each side by '2'. v = -2 Simplifying v = -2
| 2z^3+9z^2=5z | | 5b-16-8n=-10 | | 7(y+1)=49 | | K=17 | | X+3=-32 | | 15-f=-23 | | 4-5(x+3)=25 | | -22+7r=6(r-4) | | 3x+7+6x+11=90 | | 4x+1=11x | | -2(5y+5)=4 | | 3*x=10 | | 8+16=-3(5x-8) | | 9(6x-5)=279 | | 22x-16x+12=-15+3x+12+6x | | 5x-9=13-x | | 7=20 | | 120*24= | | -30+5n=4+4(1+6n) | | -4(x+8)=-3x-5 | | 4(y+5)=-6(2y-1)+4y | | x^2+8x+8=o | | -5x=5x-100 | | 0.8x+.06(x+9)=1.24 | | 8w-33=-5(w+4) | | 102=-5(3-5m) | | -6=18k | | 18=4(2+x)-15 | | 13-x=5x-9 | | 3a+3b=7 | | x^2+8x+8=10 | | 3(7+x)=27 |